Keabsahan Keputusan Penjabat Sementara Bupati Seram Bagian Timur Tentang Pengangkatan Dan Pemberhentian 5 (Lima) Karateker - Diva Agustina Rahmawati; Hendrik Salmon; Dezonda Rosiana Pattipawae (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The validity of the decision and due to the legal procedures motivated by Law Number 30 of 2014 concerning Government Administration. This Regulation regulates the legal requirements of the decision that contains elements of authorized officials, procedures and substances that are in accordance with the object of the decision.Purposes of the Research: To find out and analyze the legitimate or or not the decision issued by the Acting Temporary Regent of the Eastern Seram Regent for the cancellation of a decision letter signed by the definitive regent.Methods of the Research: This research method is normative legal research, the problem approach in this study is a conceptual legislation and approach approach, the source of the legal material used in this study is the source of primary legal material and the source of secondary legal materials, legal materials that have been collected by grouped ways.Results of the Research: The results of this study are decisions issued by the Acting Regent of the Eastern Seram Regent not fulfilling the legal requirements of a decision of the elements of the authority, procedures and substance so that the decision has the potential to be canceled or canceled with the result of the decision issued.